2018
DOI: 10.1002/cam4.1321
|View full text |Cite
|
Sign up to set email alerts
|

Significant variations in the cervical cancer screening rate in China by individual‐level and geographical measures of socioeconomic status: a multilevel model analysis of a nationally representative survey dataset

Abstract: Variations in cervical cancer screening rates in China have rarely been studied in depth. This study aimed to investigate cervical cancer screening rates in relation to both individual‐level and geographical measures of socioeconomic status (SES). Data were obtained from women aged 21 years or older by face‐to‐face interviews between August 2013 and July 2014 as part of the Chinese Chronic Diseases and Risk Factors Surveillance. The geographical variables were obtained from the 2010 Chinese population census. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 43 publications
4
64
1
4
Order By: Relevance
“…We noticed 54.1% of WLHIV were coinfected with at least one STI Ther evidence displays potential risk of pregnancy adversities and HIV mother-to-child transmission among these reproductive age women. Regular cervical screening is recommended for all women aged over 25 in China, but the actual 3 year screening rate only hovers around 20% 9. Although diagnosed women have been linked to relevant ART care, the analysis further accentuates need to scale up screening of HPV as well as other STIs among these HR women and strengthen the importance of identifying HPV16/18 in cervical screening for WLHIV as preventive measure.…”
Section: Discussionmentioning
confidence: 99%
“…We noticed 54.1% of WLHIV were coinfected with at least one STI Ther evidence displays potential risk of pregnancy adversities and HIV mother-to-child transmission among these reproductive age women. Regular cervical screening is recommended for all women aged over 25 in China, but the actual 3 year screening rate only hovers around 20% 9. Although diagnosed women have been linked to relevant ART care, the analysis further accentuates need to scale up screening of HPV as well as other STIs among these HR women and strengthen the importance of identifying HPV16/18 in cervical screening for WLHIV as preventive measure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the uptake of the screening services in China is relatively low, varying from 28% to 63% in different regions . That screening rate is particularly lower for women living in rural and remote western areas, compared to women living in developed regions in China, like Beijing (44.19%) and Zhejiang (47.22%); additionally, it is lower than those in developed countries like America (80.5%) and Italy (79.0%) …”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have showed that the low screening uptake in China is largely driven by the limited knowledge of cervical cancer risk and weak awareness on cancer screening, as well as a low educational level and discomfort associated with the screening procedure . In particular, Chinese rural women are heavily influenced by the traditional culture like Confucianism, as well as the low socioeconomic status and healthcare resources …”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is no universal, well‐organized cancer screening program in China and screening currently is limited largely to occasional opportunistic screening in urban centers with efforts being initiated to extend screening to the underserved rural population . A recent nationwide cross‐sectional and large‐scale study demonstrated that only 21.4% of Chinese women aged ≥21 years reported having ever been screened and demonstrated significant geographic variations . Furthermore, recent publications have reported that China now is considered to be a “human papillomavirus (HPV)‐heavy burden” zone in some regions, with an overall HPV prevalence of between 19.8% and 26.0% .…”
Section: Introductionmentioning
confidence: 99%